Formulation, optimization, and pharmacodynamic evaluation of chitosan/phospholipid/β-cyclodextrin microspheres - Shan L; Tao EX; Meng QH; Hou WX; Liu K; Shang HC; Tang JB; Zhang WF (Dove Medical Press, 2016)
Lu Shan,1 En-Xue Tao,2 Qing-Hui Meng,3 Wen-Xia Hou,3 Kang Liu,1 Hong-Cai Shang,4 Jin-Bao Tang,1 Wei-Fen Zhang1,4 1School of Pharmacy, Weifang Medical University, 2The Affiliated Hospital of Weifang Medical University, 3School of Nursing, Weifang Medical University, Weifang, 4Key Laboratory of Chinese Internal Medicine of Ministry of Education and Beijing, Dongzhimen Hospital, Beijing University of Chinese Medicine, Beijing, People’s Republic of China Abstract: Cholinergic neurotransmission loss is the main cause of cognitive impairment in patients with Alzheimer’s disease. Phospholipids (PLs) play an essential role in memory and learning abilities. Moreover, PLs act as a source of choline in acetylcholine synthesis. This study aimed to prepare and optimize the formulation of chitosan/phospholipid/β-cyclodextrin (CTS/PL/β-CD) microspheres that can improve cognitive impairment. The CTS/PL/β-CD microspheres were prepared by spray drying, and optimized with an orthogonal design. These microspheres were also characterized in terms of morphology, structure, thermostability, drug loading, and encapsulation efficiency. The spatial learning and memory of rats were evaluated using the Morris water maze test, and the neuroprotective effects of the CTS/PL/β-CD microspheres were investigated by immunohistochemistry. Scanning electron microscopic images showed that the CTS/PL/β-CD microspheres were spherical with slightly wrinkled surfaces. Fourier transform infrared spectroscopy and differential scanning calorimetry proved that PLs formed hydrogen bonds with the amide group of CTS and the hydroxyl group of β-CD. The learning and memory abilities of rats in the treated group significantly improved compared with those in the model group. Immunohistochemical analysis revealed that treatment with the CTS/PL/β-CD microspheres attenuated the expression of protein kinase C-δ and inhibited the activation of microglias. These results suggest that the optimized microspheres have the potential to be used in the treatment of Alzheimer’s disease. Keywords: chitosan, spray drying, microsphere, Alzheimer’s disease, phospholipids